A juridicidade das relações homoafetivas no ordenamento jurídico brasileiro - Prata, Mirela Fernandes Celestino (2010)
This study herein aims to analyze the development of the family before the society, history and the laws. The modern society has brought up new family structures which require protection from the State. Therefore, the legal norms that deal with family relationships and which are constantly changing are analyzed in order to support the needs of the society. Nevertheless, this does not always happen. In this context we find homo-affective relationships, which in spite of prejudice and discrimination are formed with the same objective of traditional family structures, that is, the pursuit of happiness and personal fulfillment of its members. To what concerns this subject, the books of authority and jurisprudence are divided; part of the jurists and judges consider that homo-affective relationships are family entities and must be treated as such. On the other hand, another group understands that homoaffective relationships are not family entities and recognize them, to what concerns asset interest, as actual companies. Homo-affective relationships are supported by neither the Federal Constitution nor the infra-constitutional laws. By analyzing the principles that rule Family Law, mainly the Principles of Equality and Human Dignity, under the specific interpretation of constitutional principles, we understand that homo-affective relationships are ruled by family law, and that the laws applicable to stable relationships are the ones applicable to such relationships, by similarity